TOOLS FOR CHILDREN FITNESS IN THE PHYSICAL EDUCATION OF PRIMARY SCHOOL PUPILS - Rymar, Olga; Solovey, Alla; Sorokolit, Nataliya; Shevtsiv, Uliana; Matviiv, Vasyl (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The results of pedagogical experiment that lasted from 2017 to 2018 are published in this research. 82 children took part in the experiment, among them were 42 boys and 40 girls. The actual age of children was nine years old. The purpose of the work was to discover the influence of fitness tools on physical development, physical preparation, psycho-emotional condition on younger school-age pupils. There was noticed a significant improvement of results of physical development according to Kettle index. In particular, it is about high level (from 16,9% to 43,1%), decreasing the average (from 54,4% to 46,8%) and especially the low level of physical development (from 28,7% to 10,1%),(p<0,05). Probably, positive changes appeared in the result of Ruffier Dickson tests, improvement indicators of intermediate level (from 4,8% to 14,1%),(p<0,05), decreasing in indicators of lower-intermediate level (from 38,4% to 16,7%),(p<0,05). The stable dynamics was noticed in the results of physical preparation (p<0,05), in particular after “30m run” exercise. Boys have got the result from 6,2±0,7sec to 5,4±0,5sec, girls - from 6,9±0,5sec to 6,1±0,5sec. The exercise “tilting torso forward from sitting position” represented result 3,9cm among boys and 5,5cm among girls; the exercise “long jump from place” represented 14,7cm among boys and 22,5cm among girls; in the exercise “shuttle running” boys got result from 11,7±1sec to 9,2±0,9sec and girls – from 12,1±1,2sec to 10,2±1 sec. What is more, positive and statistically important changes (p<0,05) where in results of pupils’ psycho-emotional condition evaluation. We have noticed increasing in levels of well-being, activeness, mood.